2018
DOI: 10.1111/soc4.12584
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting mediated activism

Abstract: In this paper, my interest is to map out central arguments in recent studies of mediated activism, identify blindspots, and call for a sociological approach to link the study of media activism to a broad conception of social change. On a subject that brings together various disciplines and fields of inquiry, a sociological sensitivity to multiple forms of media activism and social change is necessary to understand not only what activists do with media but also the contributions of mediated activism to collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…This study aims to examine LGBT groups' mediated activism during the 2018 Taiwanese referenda for marriage equality. According to Waisbord (2018), mediated activism refers to the utilization of media technologies and institutional resources for collective action, including expressing demands, giving visibility to identities, raising awareness about social problems and solutions, petitioning authorities, and advocating for policy and legal changes. As mediated activism involves tactics, goals and platforms, social media has played an essential part in disseminating the information, disinformation and misinformation for both pro-and anti-marriage equality groups this time.…”
Section: Same-sex Marriage Referendum In Taiwan: Understanding Socialmentioning
confidence: 99%
“…This study aims to examine LGBT groups' mediated activism during the 2018 Taiwanese referenda for marriage equality. According to Waisbord (2018), mediated activism refers to the utilization of media technologies and institutional resources for collective action, including expressing demands, giving visibility to identities, raising awareness about social problems and solutions, petitioning authorities, and advocating for policy and legal changes. As mediated activism involves tactics, goals and platforms, social media has played an essential part in disseminating the information, disinformation and misinformation for both pro-and anti-marriage equality groups this time.…”
Section: Same-sex Marriage Referendum In Taiwan: Understanding Socialmentioning
confidence: 99%
“…Starting with the literature review in chapter two, I put existing literature on mediated activism, social movements and feminism in conversation to give a solid foundation to my study of Ni Una Menos and its implications for media and politics. I particularly engage the arguments of media scholars who have found that communication technologies, digital and otherwise, are not only tools for expression in the public sphere but structuring elements that shape the opportunities and obstacles people face to exercise citizenship and activism (Waisbord, 2018). Scholarship on mediated activism has focused on the ways that new communication technologies have disrupted the relationship between media and collective action (Earl & Kimport, 2011).…”
Section: Structure Of the Dissertationmentioning
confidence: 99%
“…However, scholars such as Tufecki (2017) and Waisbord (2018) have noted that the enthusiasm over digital technologies and their use by contemporary social movements have resulted in naïve celebrations of digital networks as inherently emancipatory tools. Waisbord (2018) specifies that research on digital activism has focused its attention on protest and expression while ignoring "the multidimensional and longitudinal impact of networked citizenship" (p. 3).…”
Section: Structure Of the Dissertationmentioning
confidence: 99%
See 2 more Smart Citations